MANAGEMENT OF DENTAL ANTERIOR OPEN BITE WITH TONQUE THRUSTING IN GROWING PATIENT: PENATALAKSANAAN GIGITAN GIGI DEPAN TERBUKA KARENA KEBIASAAN MENDORONG LIDAH PADA PASIEN TUMBUH KEMBANG - Ervina Sofyanti (Dentika: Dental Journal, 2012)
Unfavorable growth pattern in vertical direction, heredity, digital habits, tonque function, and habitual mouth breathingare some abnormal functions that change the craniodentofacial morphology. This condition is also related with intensivebad habit that is not realized by the anterior open bite patient. Elimination of the ethiology factor and patient motivationinfluenced the success of anterior open bite correction. The aethiology of this anterior open bite can affect the treatmenttime, result, and stability of treatment. This case report describes orthodontic treatment systematically of a 17.5-year-oldboy with retrognatic profile who had thumb-sucking habit in the past, infantile swallowing, and tongue-thrusting. Thetype of anterior open bite was dental and malocclussion consisted of accentuated curve of spee at maxilla and reversedcurve of spee at mandible. The treatment started by correcting curve of spee along with instruction to keep oral muscleactivity in normal occlusal forces during orthodontic treatment. After the correction in vertical direction was achieved,four-premolar extractions were done. The result after 19-month-treatment showed overcorrection of overbite of +3.5 mm,overjet of +2 mm and tongue thrusting eliminated. In conclusion, the proper orthodontic treatment concurrently with badhabit management in growing patient will affect the treatment result and stability.